Blood Pressure, Haematological And Biochemical Characteristics Of Some Adult Nigerians - Blood samples, biochemical and haematological characteristics, adult Nigerians. (International Journal of Pharma and Bio Sciences, 2011)
Cardiovascular and other blood related diseases are fast replacing communicable diseases; therefore there is need to constantly monitor our specific deleterious parameters and their associates. In this work, blood samples were collected to determine biochemical parameters: total cholesterol (TC), high density lipoprotein- cholesterol (HDL - C), low density lipoprotein- cholesterol (LDL-C), very low density lipoprotein-cholesterol (VLDL-C), non-HDL-C, total glycerides (TG) and glucose level; and haematological parameters: per cent packed cell volume (PCV %), L-aspartate: 2-oxoglutarate subjects amino- transferase (AST), L-alanine : 2-oxoglutarate amino- transferase (ALT), alkaline phosphatase (ALP), potassium ion and urea in eighteen subjects in Akure; Southwest Nigeria using Reflotron® machine (auto analyzer) and supported with the use of questionnaire to get information on age, sex and blood pressure. Blood pressure, TC, ALP, K+ and glucose were all greater than the standard while TG, AST, ALT, urea and PCV % were within the standards among both sexes. The ratios of parameters were better predictors of diseased subjects: LDL-C/HDL-C, non-HDL-C/HDL-C, TC/HDL-C, and some ALT/AST were all greater than standards in both sexes whose respective standard values were 1.0, 3.4, <1.0. F distribution statistical analysis showed that ALT, ALT/AST and TC/HDL-C were significantly different among the sexes while TC/HDL-C, non-HDL-C/HDL-C and LDL-C/HDL-C were significantly different within the females, TC/HDL-C and TC/LDL-C within the males respectively.